Integrating GIS and AHP for land suitability analysis for urban development in a secondary city of Bangladesh - Mohit, Mohammad Abdul; Ali, Mohammad Mahmud (Faculti Alam Bina, UTM, Malaysia, 2006)
Spatial desicion making involving site selection for any particular use requires proper means to handle the multiple socio-economic factors while considering the physical suitability conditions. GIS (Geographic Information System) has been recognized as a useful decision support technology, but it does not provide means to deal with multiple decision factors. Thus, this paper develops a framework for integrating the strengths of GIS and the AHP (Analytic Hierarchy Process) to incorporate the decision maker's preferences on a range of factors in finding areas/ land suitable for urban development in a secondary city of Bnagladesh.